Resumption of Cosmetic Surgery During COVID – Experience of a Specialised Cosmetic Surgery Day-case Hospital. Issue 11 (November 2021) - Imam, Syeda Zoha; Karanasios, George; Khatib, Manaf; Cavale, Naveen; Amar, Olivier; Mayou, Bryan
Summary: The novel coronavirus outbreak (COVID-19) in 2019 resulted in the suspension of all elective hospital procedures during the height of the pandemic in the UK. The Clinic in London is one of the first day-case hospitals to resume cosmetic surgery in a post-COVID-19 clinical environment, whilst also employing the use of virtual consultations. Details of the protocol implemented by the Clinic to allow the safe resumption of cosmetic surgery are stated in this paper. The volume of procedures at the Clinic saw a significant increase post-lockdown; reasons as to why this occurred are also explored in this paper. The disruption of cosmetic practice during lockdown can be said to have resulted in a backlog of procedures once lockdown restrictions began to ease. Whilst this may be true, we believe that there are other confounding factors regarding what may have influenced the rise in cosmetic surgery during the pandemic, including the privacy of working from home and the increased exposure to video conferencing software.